A335 BILIARY ATRESIA HOME SCREENING PROGRAM IN BRITISH COLUMBIA: EVALUATION OF FIRST TWO YEARS. (1st March 2018) - Woolfson, J P; Schreiber, R; Butler, A; MacFarlane, J; Kaczorowski, J; Collet, J; Bryan, S
Abstract: Background: Biliary atresia (BA), a rare newborn liver disease (1:19, 000 births in Canada), is the leading cause of cirrhosis and liver related mortality in children. Early referral and timely surgical intervention (≤60 days of age) with a Kasai procedure (KP) offers the best chance for long-term survival without liver transplant. Taiwan has a universal BA screening program using infant stool colour cards (SCCs) with proven effectiveness. We report our experience following introduction of a similar BA screening program in BC. Aims: To assess the BC provincial BA home screening program performance and cost during the first 2 years of operation. Methods: The study period was from program launch April 1, 2014 to March 31, 2016. SCCs were distributed to families upon discharge from the maternity ward. Parents were instructed to monitor their infant's stool colour for the first month of life using photos of normal and abnormal stool colour on the SCC and contact the screening centre if concerned. Number of live births, BA cases and program costs were calculated. Frequency and reasons for contacting the centre were recorded. Card distribution was assessed by examining the number of SCCs re-ordered by maternity units compared with their number of births. Also, BC Children's Hospital charts from four 2-week periods were randomly selected between July 2015 and June 2016 to determine SCC distribution rates based on nurse sign-off of the SCC box on the discharge sheet. Analyses of sensitivity, specificity, PPV and NPV of SCC performance were performed. The UBC IRB approved the study. Results: There were 87, 583 live births through the study period and 8 cases of BA (1:10, 948). Four BA cases were identified by the SCC and four were missed. The median age of KP in the identified and missed groups was 51 and 112 days respectively. The sensitivity of the SCC was 50%, specificity 99%, PPV 5% and NPV 99%. The false positive rate was 0.08%. 126 maternity units received SCCs. Eight sites did not reorder sufficient number of SCCs based on their number of births, accounting for 2% of the provincial births. 1050 BCCH charts were reviewed. 63 did not contain a discharge record. Of the remaining 987 charts, 94% had the SCC signed off as a discharge item. Reasons for incomplete SCC sign off were early discharge and discharge sheets with multiple unsigned items. The total 2 year operational cost was 42, 600 with the SCC cost per birth being 0.48. Conclusions: This first report of the BC BA screening program showed SCC case identification was associated with earlier age of KP. However, the SCC requires modification to improve its sensitivity. Specificity and distribution rates were high and program cost was low. Further assessment of the program after 5 years will provide additional information regarding outcomes and cost effectiveness. Funding Agencies: None